Enhancing EFL University Students' Speaking Proficiency through Storynomics: A Quasi-Experimental Study - Ni Luh Supartini; Ni Made Sri Rahayu (Universitas Sarjanawiyata Tamansiswa, 2026)
This study investigates the effectiveness of a Storynomic-Based Learning Model among English as a Foreign Language (EFL) university students. The study was conducted in an English for Hospitality course at a higher education institution in Indonesia using a quasi-experimental design. Two intact classes were selected as the experimental and control groups. The experimental group was taught using the Storynomic-Based Learning Model, while the control group received conventional speaking instruction. Pre-test and post-speaking tests were conducted and assessed using a standardized rubric focusing on fluency, accuracy, pronunciation, and coherence. Results from independent samples t-tests and ANCOVA revealed that the experimental group demonstrated significantly greater improvement in overall speaking proficiency compared to the control group (p < 0.01). Qualitative feedback further indicated increased motivation, confidence, and narrative competence among students in the Storynomic group. The results suggest that the integration of storytelling, contextual hospitality narratives, and experiential speaking activities can enhance students’ speaking performance in a more meaningful and engaging way. This study contributes empirical evidence to the application of storynomic pedagogy in English for Specific Purposes (ESP) contexts, particularly hospitality education in Indonesia.